Factors Affecting The Incidence of Anemia in Third-Trimester Pregnant Women at Purwoharjo Primary Health Center, Pemalang District - Zaliyanti, Vera; Herlambang, Penggalih Mahardika; Fatmawati, Widi (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
AbstractIntroduction: Anemia in pregnancy occurs due to a lack of nutritional intake to meet the needs of the mother and fetus. According to Riskesdas, the prevalence of anemia in Indonesia is 48.9%. Anemia in pregnancy can occur due to various factors. The most common anemia in pregnancy is iron deficiency anemia which is caused by a lack of nutritional intake and foods that contain iron.Methods: This research uses a quantitative approach with descriptive observational, the sample was pregnant women in the third trimester, who had Hb levels <11 gr/dl and underwent ANC at Purwoharjo Primary Health Center. This research was conducted in August-October 2023 with a total of 62 respondents, analysis used univariate analysis.Results: The prevalence of anemia in third-trimester pregnant women at the Purwoharjo Primary Health Center is 43%. Various factors influence the incidence of anemia in pregnant women in the third trimester at Purwoharjo Primary Health Center.Conclusion: The prevalence of third-trimester pregnancy anemia at the Purwoharjo Primary Health Center is 43%, and the most influencing factors are nutritional status (61.3%) and non-compliance with iron supplement consumption (53.2%). Health officials have also made various efforts to reduce the incidence of anemia